Development Strategy for Economic Status Elevation of Sri-utumporn Community Based on Sufficiency Economy Philosophy through Systematic Approach - Wangsu, Amnaj; Lerkrai, Direk; Wongkumchan, Supawan; Sakpuram, Thavajchai (Mediterranean Journal of Social Sciences, 2012)
The research objectives were 1) to construct development strategy for economic status elevation of Sri-utumporn Community, 2) to experiment the constructed development strategy for economic status elevation based on Sufficiency-Economy Philosophy (SEP) through system approach, and 3) to determine satisfaction level of experiment group for implementation of development strategy for economic status elevation based on SEP through system approach. The research design was mixed methods of quantitative and qualitative approaches. The Multi-stage random sampling was used for sampling 102 households from 499 households of Sri-Utumpon Community, Nongkrot Subdistrict, Nakhon Sawan Province for qualitative research with focus group discussion for construction development strategy for economic status elevation based on SEP through system approach. The purposive sampling was employed for selection of experimental and control groups for Quasi-experimental research.The results were as followings: the constructed economic status elevation based on SEP comprised 4 system units included 1) raising more income, 2) reducing expenses, 3) increasing saving, and 4) paying debt gradually and regularly. The mean scores of knowledge and understanding, and acceptance of development strategy for economic status elevation based on SEP was higher than the control group at statistically significant level of 0.01. Their satisfaction level as a whole was at good level.